2010
DOI: 10.1007/s11129-010-9088-6
|View full text |Cite
|
Sign up to set email alerts
|

What makes you click?—Mate preferences in online dating

Abstract: Mate preferences, Dating, Marriage, C78, J12,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
222
2
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 357 publications
(264 citation statements)
references
References 35 publications
(65 reference statements)
20
222
2
8
Order By: Relevance
“…Prior work, by contrast, has focused on later-stage selection effects-examining who individuals choose to contact from among those whose full profiles they view-and therefore potentially misses the effect of race and other factors during the initial winnowing of the dating pool. Hitsch et al (2010), for example, find that at this later stage, men's observed behavior is in line with their stated preferences, in sharp contrast to our own finding that even those who do not state a racial preference display a strong tendency to prefer same-race candidates early in the selection process.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Prior work, by contrast, has focused on later-stage selection effects-examining who individuals choose to contact from among those whose full profiles they view-and therefore potentially misses the effect of race and other factors during the initial winnowing of the dating pool. Hitsch et al (2010), for example, find that at this later stage, men's observed behavior is in line with their stated preferences, in sharp contrast to our own finding that even those who do not state a racial preference display a strong tendency to prefer same-race candidates early in the selection process.…”
contrasting
confidence: 99%
“…Although we make no claim that our sample is representative of the general U.S. dating population (which itself differs systematically from the overall U.S. population), it does exhibit significant mass over a broad range of relevant demographics, including, for example, both younger (18-29) and older (60+) users, education levels ranging from "some high school" to "postgraduate," annual income ranging from less than $25,000 to more than $150,000, substantial populations from all regions of the country, and a variety of political affiliations, where most users describe themselves as "middle of the road." One respect in which our sample is clearly not representative of the general dating population, however, is that men are highly overrepresented 1 (75 percent)-a disparity that has been noted in other, smaller samples of online dating communities from the same era (Hitsch et al 2010).…”
Section: Datamentioning
confidence: 68%
“…However, none of this would come to be if the individuals did not like each other's profile pictures from the beginning. Pictures of the individual are very important characteristics in an online dating profile (Hitsch et al, 2010). As noted earlier, men may place greater importance on physical attractiveness conveyed through pictures compared to women (de Vries, 2010;Hitsch et al 2010).…”
Section: Online Datingmentioning
confidence: 92%
“…For example, in online contexts, men place more value on the woman's picture than the text of her profile, but women give approximately equal value to the picture and profile text (Hitsch, Hortaçsu, & Ariely, 2010;de Vries, 2010). However, Luo and Zhang (2009) point out that in face-to-face dating situations, men and women do not differ in how physical attractiveness affects their choices.…”
Section: Physical Attractivenessmentioning
confidence: 99%
See 1 more Smart Citation